Volume 5: Heat Transfer, Parts a and B 2011
DOI: 10.1115/gt2011-45284
|View full text |Cite
|
Sign up to set email alerts
|

Computational Study of Kelvin-Helmholtz Instability Created by Interaction of the Mainstream Flow and the Seal Flow in Gas Turbines

Abstract: The present paper gives a contribution to a better understanding of the emergence of Kelvin-Helmholtz instabilities (KHI) in gas turbines. In an earlier paper of the authors, the occurrence of the KHI’s near the rim cavity of a 1.5 stage gas turbine has been examined by use of CFD methods. It is shown that the KHI’s occur, when the swirl component of the hot gas flow is very strong. Due to the fact, that a high swirl is produced by the guide vanes of the first stage, this matter concerns all common gas turbine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…Therefore, the vortices in P0 should be induced by the interaction of the main flow and the purge flow. Rabs et al [ 31 ] identified the Kelvin–Helmholtz vortices near the rim cavity, which is caused by the shear of the main flow and purge flow. The vortices in P0 should be the result of the downstream propagation of the Kelvin–Helmholtz vortices, which can also be proved by the low uniform local vortex strength in these regions.…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, the vortices in P0 should be induced by the interaction of the main flow and the purge flow. Rabs et al [ 31 ] identified the Kelvin–Helmholtz vortices near the rim cavity, which is caused by the shear of the main flow and purge flow. The vortices in P0 should be the result of the downstream propagation of the Kelvin–Helmholtz vortices, which can also be proved by the low uniform local vortex strength in these regions.…”
Section: Resultsmentioning
confidence: 99%